Reliability analysis and optimal structure of series-parallel phased-mission systems subject to fault-level coverage - Peng, Rui; Zhai, Qingqinq; Xing, Liudong; Yang, Jun (IIE transactions, 2016)
Many practical systems have multiple consecutive and non-overlapping phases of operations during their mission and are generally referred to as phased-mission systems (PMSs). This article considers a general type of PMS consisting of subsystems connected in series, where each subsystem contains components with different capacities. The components within the same subsystem are divided into several disjoint work-sharing groups (WSGs). The capacity of each WSG is equal to the summation of the capacities of its working components, and the capacity of each subsystem is equal to the capacity of the WSG with the maximum capacity. The system capacity is bottlenecked by the capacity of the subsystem with the minimum capacity. The system survives the mission only if its capacity meets the predetermined mission demand in all phases. Such PMSs can be commonly found in the power transmission and telecommunication industries. A universal generating function-based method is first proposed for the reliability analysis of the capacitated series-parallel PMSs with the consideration of imperfect fault coverage. As different partitions of the WSGs inside a subsystem can lead to different system reliabilities, the optimal structure that maximizes the system reliability is investigated. Examples are presented to illustrate the proposed reliability evaluation method and optimization procedure.